Sexual differences in human cranial morphology: Is one sex more variable or one region more dimorphic?. Issue 12 (4th April 2021) - Milella, Marco; Franklin, Daniel; Belcastro, Maria Giovanna; Cardini, Andrea
Abstract: The quantification of cranial sexual dimorphism (CSD) among modern humans is relevant in evolutionary studies of morphological variation and in a forensic context. Despite the abundance of quantitative studies of CSD, few have specifically examined intra‐sex variability. Here we quantify CSD in a geographically homogeneous sample of adult crania, which includes Italian individuals from the 19th and 20th centuries. Cranial morphology is described with 92 3D landmarks analyzed using Procrustean geometric morphometrics (PGMM). Size and shape variables are used to compare morphological variance between sexes in the whole cranium and four individual regions. The same variables, plus Procrustes form, are used to quantify average sex differences and explore classification accuracy. Our results indicate that: (a) as predicted by Wainer's rule, males present overall more variance in size and shape, albeit this is statistically significant only for total cranial size; (b) differences between sexes are dominated by size and to a lesser extent by Procrustes form; (c) shape only accounts for a minor proportion of variance; (d) the cranial base shows almost no dimorphism for shape; and (e) facial Procrustes form is the most accurate predictor of skeletal sex. Overall, this study suggests developmental factors underlying differences in CSD among cranial regions; stresses the need for population‐specific models that describe craniofacial variation as the basis for models that facilitate the estimation of sex in unidentified skeletal remains; and provides one of the first confirmations of "Wainer's rule" in relation to sexual dimorphism in mammals specific to the human cranium.